The Application Of The Health Belief Model In Improving Healthy Behaviors Among Pregnant Women: A Literature Review - Haryanti, Priyani; Pandugaran, Santhna Letchmi; Aljaberi, Musheer A. (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Introduction: Maternal mortality rates around the world are still high. The first place out of 25 countries in Asia Pacific is Salomon Island with 327 per 100,000 live births, while the sustainable development goal target in 2030 is 70 per 100,000 live births. Factors influencing the high maternal mortality rate are pregnancy complications, demographics, sanitation, maternal education, and husband's education. Knowledge deficits require intervention in order to change behavior with appropriate approaches, such as the HBM (Health Belief Model). Objective: to determine changes in health behavior with the application of the Health Belief Model among pregnant women. Methods: This study used a literature review design. The databases involved in the search are Scopus, PubMed, Web of Science, Embase, and Google Scholar. Inclusion criteria: research with the topic Health Belief Model in Pregnancy, publication 2018-2023, full text Mesh terms used: health belief model AND pregnant women OR pregnancy. Result: Database extraction results obtained (n = 8) articles from 235 articles. Educational or evaluation materials that use Health Belief Model were nutrition education, prevention of anemia, preeclampsia, gestational diabetes, influenza vaccination, prevention of urinary tract infections, and acceptance of the COVID-19 vaccination. Conclusions: This review demonstrates the lack of evidence-based research to apply Health Belief Model to pregnant women. Nurses need to apply the concept of health belief model to pregnant women in future research and education.